Evaluation of a Conformationally Constrained Indole Carboxamide as a Potential Efflux Pump Inhibitor in Pseudomonas aeruginosa - Yongzheng Zhang; Jesus D. Rosado-Lugo; Pratik Datta; Yangsheng Sun; Yanlu Cao; Anamika Banerjee; Yi Yuan; Ajit K. Parhi (MDPI AG, 2022)
Efflux pumps in Gram-negative bacteria such as Pseudomonas aeruginosa provide intrinsic antimicrobial resistance by facilitating the extrusion of a wide range of antimicrobials. Approaches for combating efflux-mediated multidrug resistance involve, in part, developing indirect antimicrobial agents capable of inhibiting efflux, thus rescuing the activity of antimicrobials previously rendered inactive by efflux. Herein, TXA09155 is presented as a novel efflux pump inhibitor (EPI) formed by conformationally constraining our previously reported EPI TXA01182. TXA09155 demonstrates strong potentiation in combination with multiple antibiotics with efflux liabilities against wild-type and multidrug-resistant (MDR) P. aeruginosa. At 6.25 µg/mL, TXA09155, showed ≥8-fold potentiation of levofloxacin, moxifloxacin, doxycycline, minocycline, cefpirome, chloramphenicol, and cotrimoxazole. Several biophysical and genetic studies rule out membrane disruption and support efflux inhibition as the mechanism of action (MOA) of TXA09155. TXA09155 was determined to lower the frequency of resistance (FoR) to levofloxacin and enhance the killing kinetics of moxifloxacin. Most importantly, TXA09155 outperformed the levofloxacin-potentiation activity of EPIs TXA01182 and MC-04,124 against a CDC/FDA panel of MDR clinical isolates of P. aeruginosa. TXA09155 possesses favorable physiochemical and ADME properties that warrant its optimization and further development.